Recovery of ultra-high purity reactive magnesia from reject brine and its comparison with commercial magnesia - Dong, Haoliang (2024)
CO2 emissions and energy consumption associated with ordinary Portland cement production have increased the urgency for the development of alternative construction materials. Reactive magnesia cement (RMC) has been widely studied in the recent years due to the lower calcination temperature used during its production and its ability to permanently sequester CO2. In addition to the calcination of magnesite, reactive MgO, the main component of RMC, can also be synthesized from reject brine, which is rich in Mg2+. However, the presence of other components such as calcium in reject brine leads to the precipitation of other mineral phases together with Mg(OH)2, thereby reducing the purity of the final product. With the goal of improving the purity and yield of MgO synthesized at the end of this process, this study proposed a selective precipitation approach under a controlled pH. An optimum condition was determined for the synthesis of magnesium oxalate dihydrate with an ultra-high purity of 99.6 % and a high magnesium recovery rate of 94.1 %. Reactive MgO with a specific surface area of 30.2 m2/g was obtained after the calcination of the synthesized magnesium oxalate dihydrate at 700 °C for 2 h, which was higher than some of the commercially available MgO powders.